A 45-W Two-Stage Wireless Fast Charger Using Unregulated Inductive Power Transfer - Zhao, Peng; Zheng, Guangce; He, Rong; Liu, Yu; Fu, Minfan (IEEE journal of emerging and selected topics in industrial electronics (Print), 2021)
Most of the existing wireless offline chargers would employ redundant power conversion and isolation stages to charge a low-voltage battery, which leads to limited overall efficiency. In order to address the redundancy issue, this article proposes a wireless fast charger by using a two-stage configuration. An unregulated inductive power transfer (IPT) stage can not only offer galvanic isolation, but also provide high step-down voltage ratio, and then, only a simple buck converter is needed for voltage regulation. This article evaluates the influence of voltage gain on efficiency and voltage stress of an LCC-C compensated IPT stage. The zero-voltage-switching (ZVS) lost mechanism is also studied and evaluated by a proposed ZVS model. Finally, a 45-W fast charger prototype is designed for 264-V/12-V conversion. The measured peak efficiency is 78%, which is much higher than the Qi-based charger.